Analisis Penerapan Pendidikan Karakter Gotong Royong di Lingkungan Kelas IV SDN 04 Bawu Jepara - Iswayurani, Uun; Nichla Choirin Attalina, Syailin (Indo-MathEdu Intellectuals Journal, 2023)
This research aims to describe the attitude of mutual cooperation in the environment of Class IV students of SDN 04 Bawu Jepara to find out how environmentally friendly character education is implemented, especially in the attitude of mutual cooperation in class IV SDN Bawu Jepara. This is largely due to the era of globalization and technological advancements, which make students tend to be individualistic. Thus, with the activities: class picketing, group work and community service, it promotes an attitude of mutual cooperation among students. This research method is qualitative and descriptive in nature. The subjects of this research were 36 fourth grade students of SDN Bawu Jepara. Data collection in this research used data triangulation techniques from interviews, observations and documentation. The research results show that the process of educating the character of mutual cooperation in the fourth grade environment of SDN 04 Bawu Jepara is implemented with various activities such as: classroom picketing, group work and community service